Immobilized lipase taking sponge as carrier as well as preparation and application of immobilized lipase

Through the cross-linking technology of sponge carrier and glutaraldehyde, the problem of structural instability of immobilized lipase in extreme environments is solved, efficient catalysis and multiple reuses are achieved, and the cost is reduced.

CN119286839APending Publication Date: 2025-01-10BEIJING TECH & BUSINESS UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411581042.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing immobilized lipase carrier materials have unstable structural structures in extreme environments, low catalytic efficiency, and difficult to reuse, resulting in high costs and increased difficulty in use.

Method used

The sponge is used as a support and is modified by silane coupling agent and cross-linked with glutaraldehyde to fix the lipase to build an immobilized system with high enzyme loading, good catalytic efficiency and environmental stability.

Benefits of technology

The efficient catalysis of the sponge-lipase system is achieved, the enzyme activity remains unchanged from temperature changes, the number of reuses increases, the cost is low and the structure is stable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286839A_ABST
    Figure CN119286839A_ABST
Patent Text Reader

Abstract

The invention discloses immobilized lipase with sponge as a carrier and preparation and application of the immobilized lipase, belongs to the technical field of enzyme engineering, and provides a preparation method of the immobilized lipase with the sponge as the carrier, and the preparation method comprises the following steps: soaking the sponge in a silane coupling agent, and drying for the first time to obtain modified sponge; and mixing the modified sponge with glutaraldehyde and a lipase solution, standing, eluting, and drying for the second time to obtain the immobilized lipase. The modified sponge immobilized lipase which is high in enzyme loading capacity, high in catalytic efficiency, good in environmental stability and high in repeated use frequency is constructed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of enzyme engineering, and in particular relates to an immobilized lipase using a sponge as a carrier and the preparation and application thereof. Background Art

[0002] Lipase (EC 3.1.1.3), also known as triacylglycerol hydrolase, is a biocatalyst that is widely present in nature and plays an important role in catalyzing chemical reactions. It can catalyze a series of reactions of different substrates in aqueous or anhydrous environments, such as ester hydrolysis, ester synthesis, ester exchange, alcoholysis, acidolysis, aminolysis, amidation, and decomposition of racemates. Among them, ester hydrolysis in oil and water phases and ester synthesis in organic phases are the main reactions, which makes lipase have broad application prospects in food production and processing, drug manufacturing and medical treatment, environmental protection, beauty, biosensors, energy development and other industries. However, since free lipase can only maintain activity under specific mild conditions, its catalytic efficiency is easily affected by the external environment and cannot be stabilized, and it is difficult to recover and reuse, which increases the difficulty of use and the cost. In order to solve the above problems and expand the scope of action of lipase, many approaches have been explored, such as chemical modification, protein engineering, immobilization, etc. Among them, the immobilization of lipase has been proven to be a simple, reliable and effective method. The choice of immobilization material directly affects the core performance parameters of the immobilization system. It should have rich porosity, sufficient surface area, stable physical and chemical properties, good biological affinity, freely retractable skeleton structure, easy operation and low cost.

[0003] Furthermore, the sponge-lipase immobilization strategy should be adjusted accordingly for different reaction types of lipase. For the hydrolysis reaction of lipase, most lipases have a movable polypeptide chain, called "lid". At the hydrophobic interface, the lid moves, the catalytic position is exposed and binds to the substrate, and the enzyme activity increases, which is called interfacial activation. The more oil-water interfaces in the immobilized carrier means higher catalytic efficiency. This requires that the immobilized material has a large enough specific surface area for easy operation so that the oil-water interface can be artificially constructed later. In the esterification reaction, since there is only one organic phase, the main focus should be on the degree of binding between the substrate and the lipase and the negative impact caused by the organic solvent. The selection of high-throughput and multi-level internal structure carrier materials will not hinder the reaction and play a certain protective role on the lipase. Next, determine the appropriate immobilization method, which can be roughly divided into five types, namely adsorption, covalent binding, embedding, microencapsulation and cross-linking. Among them, the physical approach is mainly adsorption, which allows lipase to be adsorbed on the surface of the carrier material through ion binding, biospecific interaction, nonspecific interaction, hydrophobic interaction, chelation and affinity binding. This method will not affect the change of the lipase structure and maintain the activity of the lipase, but due to the weak binding force, the lipase may fall off later. The chemical approach is to form various chemical bonds between the two or achieve intermolecular aggregation through cross-linking. This method will irreversibly bind the lipase to the carrier material, greatly improving the stability of the binding, but will affect the activity of the lipase. Therefore, it is necessary to select suitable immobilization materials and immobilization methods according to the catalytic characteristics and characteristics of the lipase so that it can meet different application scenarios.

[0004] In order to achieve a specific effect, the preparation of immobilized materials involves several steps of chemical reactions and the synthesis of several chemical reagents, which is cumbersome to operate, complex to react, and costly; it is unable to maintain the stability of its own structure under extreme conditions; it is unable to ensure a good spatial configuration (space, size, particle size, porosity, etc.), resulting in low enzyme loading; among them, the mass transfer resistance affecting the water-oil flux is the main reason for the low catalytic efficiency of the immobilized enzyme; there are not enough specific sites on the carrier material for binding to the lipase, which will cause the immobilized enzyme to be susceptible to environmental influences and fall off after the reaction is completed and cannot be used again. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes an immobilized lipase with sponge as carrier and its preparation and application, and constructs an immobilized lipase with high enzyme loading, good catalytic efficiency, good environmental stability and high number of reuses.

[0006] To achieve the above object, the present invention provides a method for preparing immobilized lipase using sponge as a carrier, comprising the following steps: (1) The sponge is soaked in a silane coupling agent and then dried to obtain a modified sponge; (2) The modified sponge obtained in step (1) is mixed with glutaraldehyde and lipase solution, allowed to stand, eluted, and dried for a second time to obtain immobilized lipase.

[0007] Preferably, the sponge in step (1) is a melamine sponge; the silane coupling agent in step (1) is a toluene solution of 3-aminopropyltriethoxysilane; the soaking treatment time in step (1) is 20 to 28 hours; the first drying temperature in step (1) is 70 to 90° C., and the first drying time is 4 to 8 hours.

[0008] Further preferably, the concentration of the toluene solution of 3-aminopropyltriethoxysilane is 0.5-1.5 wt %.

[0009] Preferably, the mixing ratio of the modified sponge to the glutaraldehyde and lipase solution in step (2) is 0.5-1 cm 3 : 10~30μL: 1~3mL.

[0010] Further preferably, the concentration of the lipase solution is 8-12 mg / mL, and the lipase solution is a Burkholderia cepacia lipase solution.

[0011] Preferably, the standing time in step (2) is 20 to 40 minutes; the elution treatment in step (2) is specifically to immerse the sponge in a PBS solution and squeeze it repeatedly for 3 to 5 times; the temperature of the second drying in step (2) is 50 to 70° C., and the time of the second drying is 22 to 26 hours.

[0012] Preferably, the method further comprises the following steps: in step (2), the immobilized lipase is mixed with a PBS solution, and then the whole is immersed in a dodecane solution containing 4-nitrophenyl palmitate of oleyl glyceride, subjected to ultrasonic reaction, and then anhydrous ethanol is added to terminate the reaction, and the product obtained by the hydrolysis reaction catalyzed by the immobilized lipase is extracted with a PBS solution.

[0013] Further preferably, the concentration of olein in the dodecane solution of 4-nitrophenyl palmitate containing olein is 0.5-1.5 wt %, and the ultrasonic reaction frequency is 15-40 kHz.

[0014] The invention also provides the immobilized lipase prepared by the preparation method.

[0015] The present invention also provides the use of the immobilized lipase prepared by the preparation method as a catalyst in catalytic hydrolysis reaction and / or esterification reaction.

[0016] Compared with the prior art, the present invention has the following advantages and technical effects: The present invention proposes an immobilized lipase with a sponge as a carrier and a preparation method thereof, which is simple, efficient and low in cost. A hydrophobic group is introduced into a melamine sponge (MS) framework by a one-step impregnation method, and the lipase is fixed in the modified MS pores by physical adsorption and cross-linking, so as to construct an immobilized lipase with high enzyme loading, good catalytic efficiency, good environmental stability and high number of reuses. MS has a unique 3D mesh structure, and its porosity of about 99% makes it have an adsorption capacity several times greater than its own. The extremely large specific surface area provides a large number of attachment sites for lipase. Its chemical structure is composed of a 2,4,6-triaminotriazine skeleton. Due to the physicochemical stability of the carbon-nitrogen heterocyclic structure, MS can maintain its original structure in most environments. Compared with other immobilized carriers, MS can be purchased directly from the market at a very low price, without the need for complex chemical reaction synthesis, thus saving costs.

[0017] Specifically, MS is immersed in a 3-aminopropyltriethoxysilane (APTES) modified liquid and heat-treated to form AMS, then AMS is immersed in a lipase solution and squeezed repeatedly, and dried after being completely immersed to form AMS-lipase; the cross-linking method uses glutaraldehyde as a cross-linking agent to form AMS-GA-lipase. During the immobilization process, a Schiff base reaction occurs between the amino group of the lipase and the aldehyde group of glutaraldehyde. As a cross-linking agent, the free aldehyde groups at both ends of glutaraldehyde can react with both the amino end group of the lipase and the amino group of APTES grafted on the sponge surface.

[0018] The immobilized lipase prepared by the present invention has almost the same enzyme activity whether reacting in a low temperature or high temperature environment, and maintains the highest value at room temperature, reflecting that the sponge-lipase system has good temperature stability. In addition, compared with the dispersibility and flexibility of free enzymes, the active site of the enzyme is directly exposed to the environment, and the enzyme molecules after being immobilized with the carrier are confined between the sponge skeleton, which protects the active site of the enzyme.

[0019] Compared with ordinary physical adsorption immobilized enzymes, AMS-GA-lipase effectively increases the number of uses during repeated use, and maintains the same enzyme activity until it is used for the eighth time after being reused for three times. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1Process flow chart for preparing AMS-lipase and AMS-GA-lipase by one-step impregnation method for MS; Figure 2 Characterization diagrams of the morphology and contact angle of MS and AMS, where a is the SEM image of MS magnified 1000 times, b is the SEM image of AMS magnified 1000 times, c is the SEM image of AMS magnified 100 times, and d is the WCA image of AMS; Figure 3 Infrared spectra of MS, AMS, Lipase, and AMS-GA-lipase; Figure 4 It is the transmission electron microscopy image of AMS-GA-lipase, where a is the overall distribution TEM scanning map of AMS-GA-lipase element distribution, b is the C element area TEM scanning map, c is the N element area TEM scanning map, d is the O element area TEM scanning map, e is the Si element area TEM scanning map, and f is the P element area TEM scanning map, and the scale is 25 μm; Figure 5 Confocal laser scanning microscope analysis images, where a is the AMS-lipase confocal laser scanning water phase staining image, b is the AMS-lipase confocal laser scanning oil phase staining image, c is the AMS-lipase confocal laser scanning staining image, d is the MS-lipase confocal laser scanning image, and e is the AMS-lipase confocal laser scanning image after ultrasonic treatment, and the scale bar is 100 μm; Figure 6 The effect of cross-linking time on the enzyme loading of MS, AMS, and AMS-GA; Figure 7 This is the effect of glutaraldehyde concentration on the enzyme loading of MS, AMS, and AMS-GA; Figure 8 This is the effect of the number of desorption cycles on the enzyme loading of MS, AMS, and AMS-GA; Fig. 9 This is the effect of water-oil ratio on the enzyme activities of Lipase, MS-lipase, AMS-lipase, and AMS-GA-lipase; Fig.10 The effect of surfactant concentration on the enzyme activities of Lipase, MS-lipase, AMS-lipase, and AMS-GA-lipase; Fig.11 The effect of different ultrasonic frequencies on the enzyme activities of Lipase, MS-lipase, AMS-lipase, and AMS-GA-lipase; Fig.12The effect of different ultrasonic frequencies of adding oleylglycerol on the enzyme activities of Lipase, MS-lipase, AMS-lipase, and AMS-GA-lipase; Fig.13 The reaction diagram for the reaction of benzoic acid and benzyl alcohol to produce benzyl benzoate; Fig.14 This is a graph showing the concentration of benzyl benzoate generated by Lipase, MS-lipase, and AMS-GA-lipase versus reaction time; Fig.15 The effect of different temperatures on the enzyme activities of Lipase, MS-lipase, AMS-lipase, and AMS-GA-lipase; Fig.16 The effect of different pH on the enzyme activities of Lipase, MS-lipase, AMS-lipase, and AMS-GA-lipase; Fig.17 This is a graph showing the effect of the original treatment on the number of repeated uses of MS-lipase, AMS-lipase, and AMS-GA-lipase; Fig.18 This is the effect of surfactant treatment on the number of repeated uses of MS-lipase, AMS-lipase, and AMS-GA-lipase; Fig.19 This is a graph showing the effect of ultrasonic treatment on the number of repeated uses of MS-lipase, AMS-lipase, and AMS-GA-lipase. DETAILED DESCRIPTION

[0022] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0023] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0024] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0025] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0026] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0027] Sources of materials used in the present invention: melamine sponge was purchased from Henan Deju New Materials Co., Ltd.; toluene solution of 3-aminopropyltriethoxysilane was purchased from Shanghai McLean Biochemical Co., Ltd.; glutaraldehyde was purchased from Shanghai McLean Biochemical Co., Ltd.; Burkholderia cepacia lipase (BCL) was purchased from Sigma-Aldrich, USA (Burkholderia cepacia lipase solution is prepared by completely dissolving Burkholderia cepacia lipase in 0.1M PBS solution (pH 7)).

[0028] Example 1 (1) A melamine sponge (MS) with a radius of 12 mm and a height of 5 mm was immersed in a toluene solution of 3-aminopropyltriethoxysilane (APTES) with a concentration of 1 wt% for 24 h. After squeezing out the liquid in the sponge, it was first dried at 80 °C for 6 h to obtain a modified hydrophobic sponge (AMS). (2) AMS, glutaraldehyde and 10 mg / mL Burkholderia cepacia lipase solution were mixed at 0.75 cm 3 : 20μL: 2mL mixed, let stand for 30min, eluted once (immerse the sponge in PBS solution and squeeze it repeatedly 4 times), and dried at 60℃ for a second time for 24h to obtain immobilized lipase (AMS-GA-lipase).

[0029] Example 2 (1) A melamine sponge (MS) with a radius of 12 mm and a height of 5 mm was immersed in a toluene solution of 3-aminopropyltriethoxysilane (APTES) with a concentration of 0.5 wt% for 28 h. After squeezing out the liquid in the sponge, it was first dried at 70 °C for 8 h to obtain a modified hydrophobic sponge (AMS). (2) AMS, glutaraldehyde and 8 mg / mL Burkholderia cepacia lipase solution were mixed at 0.5 cm 3 : 1μL: 1mL mixture, let stand for 40min, elute once (immerse the sponge in PBS solution and squeeze it repeatedly 3 times), and dry it at 50℃ for a second time for 26h to obtain immobilized lipase (AMS-GA-lipase).

[0030] Example 3 (1) A melamine sponge (MS) with a radius of 12 mm and a height of 5 mm was immersed in a toluene solution of 3-aminopropyltriethoxysilane (APTES) with a concentration of 1.5 wt% for 20 h. After squeezing out the liquid in the sponge, it was first dried at 90 °C for 4 h to obtain a modified hydrophobic sponge (AMS). (2) AMS, glutaraldehyde and 12 mg / mL Burkholderia cepacia lipase solution were mixed at 1 cm 3 : 30μL: 3mL mixed, let stand for 20min, elute (immerse the sponge in PBS solution and squeeze it repeatedly 5 times) once, and dry it at 70℃ for a second time for 22h to obtain immobilized lipase (AMS-GA-lipase).

[0031] Comparative Example 1 Melamine sponge (MS) with a radius of 12 mm and a height of 5 mm was mixed with a 10 mg / mL Burkholderia cepacia lipase solution at a temperature of 0.75 mm. 3 : 2mL mixed, let stand for 30min, elute once (immerse the sponge in PBS solution and squeeze it repeatedly 4 times), and dry it at 60℃ for 24h to obtain MS-lipase.

[0032] Comparative Example 2 (1) A melamine sponge (MS) with a radius of 12 mm and a height of 5 mm was immersed in a toluene solution of 3-aminopropyltriethoxysilane (APTES) with a concentration of 1 wt% for 24 h. After squeezing out the liquid in the sponge, it was first dried at 80 °C for 6 h to obtain a modified hydrophobic sponge (AMS). (2) AMS and 10 mg / mL Burkholderia cepacia lipase solution were mixed at 0.75 cm 3 : 2mL mixed, let stand for 30min, elute once (immerse the sponge in PBS solution and squeeze it repeatedly 4 times), and dry it at 60℃ for 24h to obtain AMS-lipase.

[0033] Comparative Example 3 (1) A melamine sponge (MS) with a radius of 12 mm and a height of 5 mm was immersed in a toluene solution of 3-aminopropyltriethoxysilane (APTES) with a concentration of 1 wt% for 24 h. After squeezing out the liquid in the sponge, it was first dried at 80 °C for 6 h to obtain a modified hydrophobic sponge (AMS). (2) AMS and glutaraldehyde were mixed at 0.75 cm 3 : 20μL mixed, let stand for 30min, elute once (immerse the sponge in PBS solution and squeeze it repeatedly 4 times), and dry it at 60℃ for 24h to obtain AMS-GA.

[0034] Experimental Example 1 1. Characterization of modified sponge (1) Determination of microscopic morphology and structure The structure and morphology of the samples were characterized by scanning electron microscopy. The MS / AMS morphology sheared to an appropriate size was observed under the conditions of 5 kV accelerating voltage and 1.5 min gold spraying time.

[0035] (2) Microscopic oil-water distribution characteristics Confocal laser scanning microscopy was used to observe the distribution of samples. For observation, MS-lipase / AMS-lipase needed to be stained with Nile blue (excitation wavelength 640nm) and Nile red (excitation wavelength 488nm) dyes, respectively.

[0036] (3) Fourier transform infrared spectroscopy analysis The chemical groups of the samples were characterized by Fourier transform infrared spectroscopy. The scanning wavelength range was 400-4000cm -1 , resolution 4cm -1 The raw data of each sample were obtained using OMNIC32 (version number: 9.2.0.41) image processing software.

[0037] (4) Contact angle test (CA) Water contact angle (WCA) The optical contact angle meter was used for measurement at room temperature. The dried sample was cut into a cylinder with a diameter of 1.2 cm and dripped onto the MS / AMS surface with deionized water. The volume of the droplet was controlled to be 1 mL. The results were recorded at the moment the droplet and the sample came into contact.

[0038] (5) Results like Figure 1 As shown in Figure 1, the construction of the hydrophobic melamine sponge was carried out by immersing the MS in a 3-aminopropyltriethoxysilane solution in a one-step method, and a hydrophobic coating was formed on the sponge skeleton after hydrolysis and condensation. The construction and structural characterization (morphology and contact angle) of the hydrophobic sponge were shown in Figure 1. Figure 2 Middle a, Figure 2Middle b, Figure 2 Medium c and Figure 2 As shown in middle d, the original MS has a smooth surface (such as Figure 2 In (a), after the MS was modified by APTES, the original smooth skeleton was evenly covered by a large number of micron / scale particles, resulting in a rough surface of the AMS (e.g. Figure 2 b). The water contact angle of AMS was measured to be 122.3° ( Figure 2 (d) This is consistent with the experimental results of water absorption of 4.54%, oil absorption of 64.06% and SEM scanning. Figure 2 As shown in Figure c, MS has a rich pore structure, which provides good binding sites for the subsequent lipase immobilization, provides a certain protection for the lipase molecules, and contributes to the stability of lipase catalysis.

[0039] MS, AMS, Lipase, AMS-GA-lipase infrared spectroscopy (FTIR) analysis spectra are shown in Figure 3 As shown, for MS, it can be seen that 3318 cm -1 The stretching vibration absorption peak of NH and OH is 1564cm -1 The bending vibration absorption peak of NH and the stretching vibration absorption peak of C=N are at 1474cm -1 The bending vibration absorption peak of -CH2- is 1332cm -1 The stretching vibration absorption peak of CN is at 2950cm -1 The stretching vibration absorption peak of CH of APTES is 991 cm -1 The bending vibration absorption peak of Si-OH is 808cm -1 The peaks at 3390cm are the symmetrical stretching vibration absorption peaks of Si-O. The appearance of these characteristic peaks confirms that APTES is successfully grafted onto the MS framework. For AMS-GA-lipase, it can be seen that the lipase peak at 3390cm -1 The stretching vibration absorption peak of NH at 2292 cm -1 The antisymmetric stretching vibration absorption peak of -CH2- is 1647cm -1 and 1371cm -1 Amide I (C=O stretching vibration) and amide II (NH bending vibration and CN stretching vibration) -573cm -1 The stretching vibration absorption peak of CH appears at 1467 cm -1The absorption peak is due to the vibration of C=N on the propyl chain of glutaraldehyde, which indicates that during the immobilization process, a Schiff base reaction occurred between the amino group of lipase and the aldehyde group of glutaraldehyde. Glutaraldehyde is used as a crosslinker, and the free aldehyde groups at both ends can react with both the amino end group of lipase and the amino group of APTES grafted on the sponge surface. At the same time, as an AMS, the peak at 1564cm -1 、1474cm -1 、808cm -1 The main characteristic peak did not disappear, confirming that the lipase was successfully cross-linked to AMS.

[0040] like Figure 4 Figure 2 shows a transmission electron microscopy image of AMS-GA-lipase. Figure 4 Middle b, Figure 4 Middle c, Figure 4 Middle d, Figure 4 Zhongehe Figure 4 As shown in the middle f, C, N, O, Si, and P elements were detected on the AMS, and the contents were 46.81%, 21.23%, 27.84%, 1.14%, and 2.54%, respectively. This clearly shows that APTES successfully modified the surface of MS. Figure 4 In middle a, it is clearly shown that a large number of S and P elements unique to lipase are dispersed on the AMS, which, combined with the infrared spectrum, once again proves that the lipase molecules are bonded to the AMS surface.

[0041] like Figure 5 As shown in the figure, it is the result of confocal laser scanning microscopy analysis. In the CLSM evaluation, Figure 5 In a, the aqueous phase appears blue after being stained with Nile blue. Figure 5 In b, the oil phase appears red after being stained with Nile red. Figure 5 In middle c, the blue area occupies the entire background, and the red area is evenly distributed on the sponge skeleton, such as Figure 5 In middle d, there is a clear boundary between the blue area and the red area, e.g. Figure 5 In e, the red area is spread over the entire image against a blue background. Figure 5 In c and Figure 5 In middle d, after the MS was modified with APTES, it showed hydrophobic properties on the surface of the sea skeleton. Figure 5 In d and Figure 5 In middle e, the oil-water single interface is broken up after ultrasonic treatment. The above two points will promote the binding of lipase and substrate and play a positive role in the catalytic reaction.

[0042] Due to the "interfacial activation" effect of BCL, the lid structure opens at the oil-water interface, the catalytic site is exposed and binds to the substrate, and high catalytic efficiency is achieved. In order to achieve higher catalytic efficiency, it is necessary to construct a rich oil-water interface. Through silanization with low surface energy organosilane, an oil-water interface is artificially constructed on the MS skeleton, such as Figure 5 As shown in c, after APTES modification, the MS skeleton is hydrophobic. In the aqueous environment where the lipase is located, the oil phase containing the substrate is distributed on the sponge skeleton. Figure 5 The monolayer water-oil interface of the original MS shown in middle d. AMS constructs a large number of oil-water interfaces on the skeleton, breaking the limitation of a single interface on the catalytic reaction of lipase and improving the catalytic efficiency of the whole system. Amination introduces free amino groups to react with the aldehyde group of glutaraldehyde to undergo Schiff base reaction and cross-link with the amino group of lipase. At the same time, a large number of positively charged amino groups help electrostatically attract negatively charged enzymes.

[0043] 2. Determination of enzyme loading Immerse the entire MS / AMS / AMS-GA in PBS, squeeze it repeatedly until it is completely soaked in the solution, and then calculate the water absorption rate (%) of the sample according to the following formula: Water absorption rate of sample (%) = (M T -M0) / M0×100%; Among them, M T represents the mass of the sample after water absorption (g), and M0 represents the mass of the sample before water absorption (g).

[0044] According to the BCA process, using bovine serum albumin as a standard, the MS / AMS / AMS-GA was immersed in 3 mL, 10 mg / mL lipase / lipase glutaraldehyde solution, squeezed and taken out after being completely immersed in the solution. The enzyme loading (mg / g) was indirectly determined by the difference between the mass of lipase in the remaining enzyme solution and the mass of lipase initially added according to the following formula: ; Where M1 represents the mass of lipase initially dissolved in PBS (mg), M Lipase represents the mass of lipase solution (g), C T represents the lipase concentration (mg / mL) in the remaining lipase solution determined by the BCA kit. Since the effect of the very small amount of lipase dissolved in PBS on the density of PBS is negligible, ρ Lipase =ρ PBS =1.016g / mL.

[0045] The results are as follows Figure 6 , Figure 7 and Figure 8 As shown, Figure 6As shown in the figure, at 30 minutes, the enzyme loading reached the maximum value and remained unchanged. The numerical values ​​show that the physical adsorption enzyme loading is about 400 mg / g, and the cross-linked enzyme loading is about 4-5 times that of physical adsorption, about 2300 mg / g. Compared with other types of immobilized enzymes, MS has the characteristics of light weight and large pores (1cm 3 In addition, the enzyme loading of AMS and MS is equal, which proves that APTES modification has no effect on the enzyme loading, while the increase in the enzyme loading of AMS-GA reflects that the APTES modification successfully reacts with glutaraldehyde, and APTES does not fall off during the elution process. Figure 7 As shown, with the increase of glutaraldehyde concentration, the enzyme loading reached a maximum at 1 wt% and then remained constant.

[0046] 3. Determination of shedding rate After multiple extrusion, oscillation, and ultrasonic treatment of MS-lipase / AMS-lipase / AMS-GA-lipase, the protein concentration in the remaining solution was directly determined according to the BCA process using bovine serum albumin as the standard. This process was repeated three times. The shedding rate was defined as the ratio of the protein concentration in the remaining solution to the total protein concentration, and the shedding rate (%) was calculated using the following formula: ; Where C' T It represents the lipase concentration (mg / mL) in the remaining lipase solution of the experimental group determined by the BCA kit.

[0047] like Figure 8 As shown, after one elution, the enzyme loading reached a stable value, which is the amount of enzyme immobilized on the sponge carrier. Only a trace amount of residue was detected in the subsequent elution operation, reflecting a low shedding rate of the immobilized enzyme.

[0048] 4. Effect of water-oil ratio on enzyme activity Add 50~300μL of PBS solution (0.1M, pH=7) to MS-lipase / AMS-lipase / AMS-GA-lipase, and immerse the whole in an excess of 1mL of 4-nitrophenyl palmitate (p-NPP) in dodecane solution after complete absorption. After reacting for 30 minutes, add 1mL of anhydrous ethanol to terminate the reaction. Use PBS solution (0.1M, pH=7) to completely extract the product (p-NP), spot it on a 96-well plate and put it into the microplate reader. Measure the enzyme activity at 410nm, and obtain the product (p-NP) concentration by comparing it with the standard curve. The amount of enzyme required to convert 1 micromole of substrate in 1min is one enzyme activity unit (U).

[0049] like Fig. 9As shown in the figure, due to the existence of the lid structure of lipase, different water-oil ratios will affect the interfacial area, and thus affect the catalytic efficiency. The prepared immobilized enzyme was added to the oil-water system with different ratios. The enzyme activity was the highest when the water-oil ratio was 100:1000. At a lower ratio, the water-oil contact area was smaller. At a high ratio, the enzyme was dispersed in the water phase and failed to concentrate at the interface between the two phases, and could not perform effective catalysis.

[0050] 5. Effect of surfactants on enzyme activity Add 100 μL of PBS solution (0.1M, pH=7) to MS-lipase / AMS-lipase / AMS-GA-lipase, and immerse the whole in an excess of 1 mL of dodecane solution containing 2~20wt% oleylglycerol 4-nitrophenyl palmitate (p-NPP) after complete absorption. After reacting for 30 minutes, add 1 mL of anhydrous ethanol to terminate the reaction. Use PBS solution (0.1M, pH=7) to completely extract the product (p-NP), spot it on a 96-well plate and put it into the microplate reader. Measure the enzyme activity at 410 nm. The product (p-NP) concentration is obtained by comparing with the standard curve. The amount of enzyme required to convert 1 micromole of substrate in 1 minute is one enzyme activity unit (U).

[0051] like Fig.10 As shown, by adding olein to the reaction as a W / O type, the monolayer oil-water interface is broken to form an "oil-in-water" structure. The effects of surfactants on catalytic efficiency at different concentrations were compared. At different concentrations, as the amount of olein added increased, the enzyme activity increased from low to high and then to low, reaching a maximum at 5wt%. The enzyme activity of MS-lipase / AMS-lipase / AMS-GA-lipase without the addition of olein was increased by 1.8-2.2 times, and the enzyme activity of free enzyme was increased by 3-3.5 times. In summary, it can be seen that the oil-in-water system formed by a small amount of water phase under the premise of excess oil phase forms a two-phase interface more fully, but the excessive addition of surfactants hinders the contact between the two phases and inhibits the overall reaction.

[0052] 6. Effect of ultrasonic treatment on enzyme activity 100 μL of PBS solution (0.1M, pH=7) was added to MS-lipase / AMS-lipase / AMS-GA-lipase. After complete absorption, the whole was immersed in an excess of 1 mL of dodecane solution containing / without 1 wt% oleylglycerol 4-nitrophenyl palmitate (p-NPP). The reaction was carried out in an ultrasonic cleaner at a frequency of 16-40 kHz for 30 min, and 1 mL of anhydrous ethanol was added to terminate the reaction. The product (p-NP) was completely extracted with PBS solution (0.1M, pH=7), spotted on a 96-well plate and placed in an ELISA reader. The enzyme activity was measured at 410 nm. The product (p-NP) concentration was obtained by comparison with the standard curve. The amount of enzyme required to convert 1 micromole of substrate in 1 min is one enzyme activity unit (U).

[0053] The results are as follows Fig.11 and 12 As shown in the figure, after ultrasonic treatment, the enzyme activity of MS-lipase / AMS-lipase / AMS-GA-lipase and free enzyme was significantly improved, which was 4.5-5 times higher than that of the enzyme without ultrasonic treatment. Ultrasonic treatment at low frequency after adding oleylglycerol significantly improved the enzyme activity. Combining the two analyses, it may be because the external physical effect promotes the combination of oil phase, water phase and enzyme, creates more oil-water interfaces, and provides lipase with more opportunities to contact the substrate. In addition, due to the large-pore network structure of the sponge, when external physical means are intervened, the stability of the carbon-nitrogen heterocyclic skeleton itself keeps the shape of the whole system unchanged, produces more and more stable two-phase interfaces, and enables more enzymes free in the two phases to bind to the substrate at the interface, thereby improving the catalytic efficiency.

[0054] 7. Enzymatic esterification reaction Dissolve benzoic acid in dimethyl sulfoxide and benzyl alcohol in a molar ratio of 1:1, add 5 mg MS-lipase / AMS-GA-lipase, and react at 60°C with stirring for 5-24 hours. After the reaction is completed, take the mixture, spot it on a 96-well plate and put it into an ELISA reader. Measure the absorbance at 410 nm. Compare it with the standard curve to obtain the concentration of benzyl benzoate.

[0055] like Fig.13 As shown in Figure 1, the esterification reaction synthesizes the edible flavor benzyl benzoate, which expands the application potential in the food field. Fig.13As shown in the figure, at a lipase dosage of 5 mg, as the reaction time progresses, the concentration of benzyl benzoate reaches a peak at 12 h and then remains constant and slightly decreases. It can be seen that the efficiency of the MS-lipase / AMS-GA-lipase catalytic reaction is significantly better than that of the free lipase at equal amounts. This is due to the protection of the MS skeleton on the enzyme active site and the chemical cross-linking of glutaraldehyde and the enzyme molecules, which further improves the stability of the sponge-lipase system in organic solvents.

[0056] 8. Environmental stability test Add 100μL of PBS solution (0.1M, pH=7) to MS-lipase / AMS-lipase / AMS-GA-lipase, and immerse the whole in an excess of 1mL of 1wt% Q12S 4-nitrophenyl palmitate (p-NPP) in dodecane solution after complete absorption. After reacting at -20~80℃ for 30min, add 1mL of anhydrous ethanol to terminate the reaction. Use PBS solution (0.1M, pH=7) to completely extract the product (p-NP), spot it on a 96-well plate and put it into an enzyme reader. Measure the enzyme activity at 410nm. The product (p-NP) concentration is obtained by comparing with the standard curve. The amount of enzyme required to convert 1 micromole of substrate in 1min is one enzyme activity unit (U).

[0057] Add 100 μL of PBS solution (0.1M, pH=4.5-9) to MS-lipase / AMS-lipase / AMS-GA-lipase, and immerse the whole in an excess of 1 mL of 1wt% oleylglycerol 4-nitrophenyl palmitate (p-NPP) in dodecane solution after complete absorption. After reacting for 30 minutes, add 1 mL of anhydrous ethanol to terminate the reaction. Use PBS solution (0.1M, pH=7) to completely extract the product (p-NP), spot it on a 96-well plate and put it into an enzyme reader. Measure the enzyme activity at 410 nm. The product (p-NP) concentration is obtained by comparing with the standard curve. The amount of enzyme required to convert 1 micromole of substrate in 1 minute is one enzyme activity unit (U).

[0058] like Fig.15As shown in the figure, the stability of the immobilized enzymes at different temperatures was measured by physical adsorption and cross-linking. The free enzyme almost stopped reacting at low temperature. As the temperature rose to 40°C, the activity of the free enzyme reached the maximum value and then gradually decreased. The activity of the immobilized enzyme remained almost unchanged regardless of whether it was reacted in a low or high temperature environment, and it maintained the highest value at room temperature, reflecting that the sponge-lipase system has good temperature stability. In addition, the temperature tolerance of the entire system is also related to the carrier structure. Compared with the dispersion and flexibility of the free enzyme, the active site of the enzyme is directly exposed to the environment. After being immobilized on the carrier, the enzyme molecules are confined between the sponge skeleton, which protects the active site of the enzyme.

[0059] like Fig.16 As shown, the stability of the immobilized enzymes by physical adsorption and cross-linking at different temperatures was measured. Compared with the free enzyme, the enzyme activity first increased and then decreased, and the MS-lipase / AMS-lipase / AMS-GA-lipase types hardly changed with pH changes. The maximum value decreased by about 25%-30% compared with pH=7. This may be due to the high throughput of MS. The dense pore network can block the impact of temperature changes, but cannot completely avoid the impact of changes in the liquid environment. In summary, it shows that the sponge-lipase system can still catalyze the hydrolysis reaction normally under some extreme environments.

[0060] 9. Number of times of repeated use Add 100 μL of PBS solution (0.1M, pH=7) to MS-lipase / AMS-lipase / AMS-GA-lipase, and after complete absorption, immerse the whole in an excess of 1 mL of dodecane solution containing / without 1 wt% oleylglycerol 4-nitrophenyl palmitate (p-NPP), react at a frequency of 0-40 kHz for 30 min in an ultrasonic cleaner, and add 1 mL of anhydrous ethanol to terminate the reaction. Use PBS solution (0.1M, pH=7) to completely extract the product (p-NP), and repeat the above operation 1-8 times. Spot on a 96-well plate and place it in an ELISA reader. Measure the enzyme activity at 410 nm. The product (p-NP) concentration is obtained by comparing with the standard curve. The amount of enzyme required to convert 1 micromole of substrate in 1 min is one enzyme activity unit (U).

[0061] The results are as follows Fig.17 , Fig.18 and Fig.19 As shown, for MS-lipase / AMS-lipase / AMS-GA-lipase without other optimization treatments, such as Fig.17As shown, the enzyme activity of MS decreased significantly after being used 8 times, the enzyme activity of AMS-liapse was the highest, and gradually decreased with the increase in the number of uses, and the enzyme activity of AMS-GA-lipase remained basically unchanged after being used three times, but there was a problem of low enzyme activity.

[0062] For MS-lipase / AMS-lipase / AMS-GA-lipase with added surfactant, Fig.18 As shown in the figure, the overall enzyme activity of the three has been improved compared with the previous group. The enzyme activity of MS-lipase and AMS-lipase gradually decreased with the increase in the number of uses, among which the decline of MS was the largest. After five uses, the enzyme activity of AMS-GA-lipase using the cross-linking method remained stable at the highest level among the three, still reaching about 4 times that of the free enzyme.

[0063] For MS-lipase / AMS-lipase / AMS-GA-lipase with the addition of surfactant and ultrasonic treatment, Fig.19 As shown in the figure, adding ultrasound assistance on the basis of the above experiment further promoted the combination of oil and water, produced more oil-water interfaces, and further increased the maximum enzyme activity when reused 1-3 times. However, since physical means will cause the enzyme to fall off through physical adsorption or cross-linking on the MS framework, it will be free in the oil and water phases and cannot effectively catalyze. Compared with the above experiment, the enzyme activity decreases significantly with the increase in the number of uses.

[0064] In summary, hydrophobic modification of MS into AMS effectively improved the enzyme activity during repeated use, and after 8 uses without optimization, adding surfactants and ultrasonic treatment, it was still 2.5, 3.5, and 3 times that of the free enzyme. The cross-linking method was then used to form AMS-GA-lipase, which effectively increased the number of uses during repeated use, and maintained the same enzyme activity until the 8th use after being reused 3 times.

[0065] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing immobilized lipase using sponge as a carrier, characterized in that: The following steps are involved: (1) The sponge is soaked in a silane coupling agent and then dried to obtain a modified sponge; (2) The modified sponge obtained in step (1) is mixed with glutaraldehyde and lipase solution, allowed to stand, eluted, and dried for a second time to obtain immobilized lipase.

2. The preparation method according to claim 1, characterized in that: The sponge in step (1) is a melamine sponge; the silane coupling agent in step (1) is a toluene solution of 3-aminopropyltriethoxysilane; the soaking treatment time in step (1) is 20 to 28 hours; the first drying temperature in step (1) is 70 to 90° C., and the first drying time is 4 to 8 hours.

3. The preparation method according to claim 2, characterized in that: The concentration of the toluene solution of 3-aminopropyltriethoxysilane is 0.5-1.5 wt %.

4. The preparation method according to claim 1, characterized in that: The mixing ratio of the modified sponge, glutaraldehyde and lipase solution in step (2) is 0.5~1cm 3 : 10~30μL: 1~3mL.

5. The preparation method according to claim 4, characterized in that: The concentration of the lipase solution is 8-12 mg / mL, and the lipase solution is a Burkholderia cepacia lipase solution.

6. The preparation method according to claim 1, characterized in that: The standing time in step (2) is 20 to 40 minutes; the elution treatment in step (2) is specifically to immerse the sponge in a PBS solution and squeeze it repeatedly for 3 to 5 times; the temperature of the second drying in step (2) is 50 to 70° C., and the time of the second drying is 22 to 26 hours.

7. The preparation method according to claim 1, characterized in that: The following steps are also included: In step (2), the immobilized lipase is mixed with a PBS solution, and then immersed in a dodecane solution containing 4-nitrophenyl palmitate of oleyl glyceride, subjected to ultrasonic reaction, and then anhydrous ethanol is added to terminate the reaction. The product obtained by the hydrolysis reaction catalyzed by the immobilized lipase is extracted with a PBS solution.

8. The preparation method according to claim 7, characterized in that: The concentration of olein in the dodecane solution of 4-nitrophenyl palmitate containing olein is 0.5-1.5wt%, and the ultrasonic reaction frequency is 15-40kHz.

9. The immobilized lipase prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the immobilized lipase prepared by the preparation method according to any one of claims 1 to 8 as a catalyst in catalytic hydrolysis reaction and / or esterification reaction.

Citation Information

Cited By

  • Magnetic carbon dots-cnc composite immobilized lipase and application thereof in synthesis of flavor ester

    CN122772858A